Too hot to handle: how Martial Eagles (Polemaetus bellicosus) manage the heat in the Kruger National Park, South Africa - Walker, Kyle (Department of Biological Sciences, 2025)
Climate change poses a serious threat to biodiversity across the globe. Shifting weather patterns and increasing temperatures present serious challenges to species' ability to persist in an environment. However, how species react to changing climatic conditions can vary between species, with some species better able to adapt to such changes than others, either through physiological processes or behavioural adaptation. Changing climatic conditions can alter a species' ability to acquire the resources they need to survive, but the mechanism of how this occurs can be complex. For predatory species, in particular, we do not have a good understanding of how different climatic conditions may affect predator-prey interactions, which may be key to understanding how well a species can persist in the future. The ability of predators to cope with a changing climate may be influenced by the level of specialism in their diet, with more generalist species expected to be better able to cope with changes in climate than more specialised species because they can in theory, switch between prey. By contrast, predatory species with more specialised diets may be more vulnerable to the effects of climate change, should the availability of their key prey species be strongly affected by climatic conditions, since they may have limited opportunities to switch to an alternative food source. However, empirically, we know little about how predator species switch between different prey types under different climate conditions. In this study, we explore the influence of climate on the ability of a generalist predator, the Martial Eagle (Polemaetus bellicosus), to provision prey and how their diet varies with climate conditions. We installed cameras to remotely monitor nests in the Kruger National Park, where previous studies revealed a large population decline and where temperatures during the breeding season have increased dramatically over the last few decades. We recorded a total of 772 camera trap days (9312 hours) during the chick rearing period from 12 nests between 2018 to 2022. Cameras took photos every five minutes, and these photographs were then assessed to identify occurrences of prey deliveries (n=793). Where possible, prey items were identified down to the lowest possible taxonomic level (n = 751). We then explored how maximum daily temperature (Tmax) and occurrence of rainfall (Rday) influenced prey provisioning and the overall biomass delivered to a nest per day. Prey provisioning rates peaked at around 1.4 items delivered on days with a Tmax of 25°C but then declined with increasing temperatures to around half that value when temperatures exceeded 40°C. However, despite fewer food items being delivered in hotter conditions, biomass delivered per day did not show a corresponding decline, remaining stable across the temperature gradient. These contrasting patterns were explained by the relationship between the average size of the prey items delivered in relation to temperature, with heavier prey items being delivered in hotter conditions. Thus, this species appeared to be able to buffer the negative influence of higher temperatures on prey captures by shifting to predate large prey items. To further explore these results, we assessed the delivery likelihood of each phylum of prey (reptiles, mammals or birds) in relation to climatic conditions. We found that in hotter conditions, the types of prey delivered shifted with fewer birds and more reptiles being delivered. Mammals on the other hand were not influenced by climatic variables. Reptile prey (principally monitor lizards, Varanus spp.) was significantly larger than bird prey, and explained the apparent increase in prey size at higher temperatures. These results indicate that the dietary requirements of Martial Eagle may be potentially buffered from the effects of climate change through their ability to provision a wide diversity of prey. These differences are most likely due to these prey types having differing physiological and behavioural responses across the temperature gradient. However, the impact of dietary shifts such as this on Martial Eagles are not entirely clear, because it may be that reptile prey is lower quality compared to bird prey and this dietary shift may influence the fitness of the developing chicks and could have longer term impacts on their subsequent fitness, which would not be immediately evident without considerable further work.